Planejamento estratégico : uma investigação da prática nas empresas do setor metalmecânico da serra gaúcha - Neumann, Susana Elisabeth (My University, 2014)
Nowadays business organizations are inserted into a complex, mutable, interconnected, and turbulent environment, signaling the need to use strategies that can guide which direction to go and help administrators to focus. With the continuously growing globalization of markets and the gradual increase in competition, strategic planning can offer positive results like profitability, innovation, creation and maintenance of a competitive advantage indispensable elements for a long term survival. However, this process, of a formal and complex application, requires time and dedication from the administrators for its development, implementation, assessment and control and corrective actions. It is in that perspective that this work is embedded, having as its objective to investigate the practices related to the process of strategic planning in small, medium and large size companies from the metal-mechanical sector of Serra Gaúcha - considered the second largest hub in Brazil. A survey instrument was used to investigate how the 361 companies practice those four stages of the strategic planning process in the light of the literature. A quantitative research was used. Data analysis was performed to identify the factors for the specific objectives. Data collection resulted in a sampling of 244 respondent companies, out of which 150 do not practice strategic planning. Therefore, after the data analysis, the main results from the 94 companies that put the strategic planning process into practice indicate that 96% of the companies studied practice the elaboration stage, 79% practice the implementation stage, 76% practice the assessment and control stage, and 76% practice the corrective action stage. However, the large size companies practice the assessment and control stage in a higher degree in comparison to small size companies, and the companies with the best billing results practice a more rigorous assessment and control stage and the corrective action of the strategic planning process. Moreover, 89% of the companies researched find that the degree of strategic planning is fundamental for the results obtained by the firm, regardless of the performance, size or number of employees.
Atualmente, as organizações empresariais estão inseridas em um ambiente complexo, mutável, interconectado e turbulento, sinalizando a necessidade do uso de estratégias que norteiem a direção e o foco de seus administradores. Com a crescente globalização de mercados e o aumento gradativo da concorrência, o planejamento estratégico pode propiciar às organizações resultados positivos tais como rentabilidade, inovação, criação e manutenção de vantagem competitiva elementos indispensáveis à sobrevivência em longo prazo. Porém, esse processo, de aplicação formal e complexa, demanda tempo e dedicação dos administradores em sua elaboração, implementação, avaliação e controle e ação corretiva. É nessa perspectiva que este trabalho se insere, tendo como objetivo investigar as práticas relativas ao processo de planejamento estratégico nas empresas de pequeno, médio e grande porte do setor metalmecânico da Serra Gaúcha considerado o segundo maior polo do Brasil. Para tal, um instrumento de pesquisa foi aplicado em 361 empresas para identificar como praticam essas quatro etapas do planejamento estratégico à luz da literatura. Assim, utilizou-se a pesquisa quantitativa, com a análise dos dados através da estatística univariada e multivariada para identificar os fatores para os objetivos específicos. A coleta de dados resultou em uma amostra de 244 empresas respondentes, sendo que 150 não aplicam o planejamento estratégico atualmente. Assim, procedeu-se a análise dos dados, sendo que os principais resultados com as 94 empresas que praticam o processo de planejamento estratégico indicam que 96% das empresas estudadas praticam a etapa de elaboração, 79% a de implementação, 76% a de avaliação e controle e 76% praticam a ação corretiva. Porém, as empresas de grande porte praticam em maior grau a etapa de avaliação e controle se comparadas com as de pequeno porte e as empresas com os melhores resultados no faturamento efetuam com maior rigor a etapa de avaliação e controle e a ação corretiva do processo de PE. Além disso, 89% das empresas pesquisadas consideram fundamental o grau de contribuição do planejamento estratégico para os resultados da empresa, independente da atuação, porte ou quantidade de funcionários.
Keywords: Administração; Planejamento estratégico; Estratégia empresarial; Estratégia competitiva; Indústria metal-mecânica; Serra gaúcha, Região (RS); Administração de empresas; Strategic planning; Entrepreneurial strategy; Competitive strategy; Industrial management